Metabolic Background Determines the Importance of NOS3 Polymorphisms in Restenosis after Percutaneous Coronary Intervention: A Study in Patients with and without the Metabolic Syndrome. Issue 2 (3rd June 2013) - Pons, Douwe; Monraats, Pascalle S.; Zwinderman, Aeilko H.; de Maat, Moniek P. M.; Doevendans, Pieter A. F. M.; de Winter, Robbert J.; Tio, René A.; Waltenberger, Johannes; Jukema, J. Wouter
Abstract : Variation in the NOS3 gene has been related to the development of restenosis. The Glu298Asp polymorphism has previously been investigated for its effect on NO levels and the development of restenosis. However, the variability of findings gave rise to the hypothesis that the functional significance of this polymorphism may only become manifest under conditions of endothelial dysfunction. Since patients with the metabolic syndrome are known to have endothelial dysfunction, we aimed to investigate if the significance of NOS3 polymorphisms may depend on the presence of the metabolic syndrome. We examined the impact of the -949 A/G, the -716 C/T and the Glu298Asp polymorphisms in the NOS3 gene on the risk of clinical restenosis in a previously described subpopulation of the GENDER-study, a multicenter prospective study design that enrolled consecutive patients after successful PCI. This subpopulation consisted of 901 patients of whom sufficient data were available to establish absence or presence of the metabolic syndrome. Of these patients, 448 had the metabolic syndrome. Clinical restenosis, defined as target vessel revascularization (TVR), was the primary endpoint. We demonstrated that the minor -949G, -716T and 298Asp alleles were associated with a significantly increased risk of TVR in patients with the metabolic syndrome (HR: 1.58 [95%CI: 1.04–2.40], HR: 1.95 [95%CI: 1.02–3.70] and HR: 1.67 [95%CI: 1.09–2.54], respectively). In the group without the metabolic syndrome we observed no association between the three polymorphisms and TVR.